2004
DOI: 10.21273/hortsci.39.3.512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium and Magnesium on Plant Growth, Biomass Partitioning, and Fruit Yield of Winter Greenhouse Tomato

Abstract: Tomato (Lycopersicon esculentum Mill) `Trust' was grown on rockwool with nutrient solutions containing two levels of calcium (150 and 300 mg·L-1) in factorial combination with three levels of magnesium (20, 50, and 80 mg·L-1) in Winters 1997 and 1998, to investigate the effects of calcium and magnesium on growth, biomass partitioning, and fruit production. Plants grown at 20 mg·L-1 Mg started to show Mg deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 17 publications
3
41
1
Order By: Relevance
“…In fact, these authors pointed out that the correlation between the exchangeable-K content and the calcium carbonate in the soil proved significant and negative. However, we did found no antagonism between soil Ca and the absorption of Mg, as might be expected (Binkley, 1993;Hao and Papadopoulos, 2004;Mendoza et al, 2014). Unexpectedly, Ca and Mg were positively correlated, confirming our speculation about their participation in the same physiological mechanisms and the plant-soil interactions.…”
Section: Nutrient Relationshipssupporting
confidence: 87%
“…In fact, these authors pointed out that the correlation between the exchangeable-K content and the calcium carbonate in the soil proved significant and negative. However, we did found no antagonism between soil Ca and the absorption of Mg, as might be expected (Binkley, 1993;Hao and Papadopoulos, 2004;Mendoza et al, 2014). Unexpectedly, Ca and Mg were positively correlated, confirming our speculation about their participation in the same physiological mechanisms and the plant-soil interactions.…”
Section: Nutrient Relationshipssupporting
confidence: 87%
“…The imbalance of mineral ions other than Ca in the nutrient solution can affect Ca uptake by the roots and its transport within the plant (Willumsen et al, 1996), especially elements that antagonise Ca uptake, as has been reported for Na (del Amor et al, 2001), K (Adams, 2002) or Mg (Hao & Papadopoulos, 2004).…”
Section: Accumulation Of Macronutrients and Trace Elements In Birch Smentioning
confidence: 82%
“…7b). Studies have indicated that there is a significant antagonistic effect of Mg on Ca uptake in tomatoes (Hao and Papadopoulos, 2004). These authors reported that when Ca concentration is low, increasing Mg concentration in the nutrient solution linearly increased the BER incidence in tomatoes.…”
Section: Discussionmentioning
confidence: 99%